Powołanie człowieka do szczęścia w nauczaniu Grzegorza Wielkiego - Kashchuk, Oleksandr (Vox Patrum, 2008)
The article discusses a ąuestion of the celestial happiness as a certain State, into which, according to the teaching of Gregory the Great, the human being was called by God and which was given to him/her as a gift. From the beginning of his/her existence, the human enjoyed the happiness of paradise and could achieve, in futurę, the higher State of happiness, which was the celestial happiness, on the condition that he/she will be obedient to God’s commandment. However, the human did not observe obedience towards God and not only did the human not achieve the higher State of happiness, but also lost the happiness of paradise. The human being, on his/ her own, could not regain the possibility of achievement of celestial happiness. The necessary condition was God’s action. Creator did not change the divine plan towards the human being and still desired him/her to be happy. God accepted the human body and redeemed humanity. God restored the human being not only to the former glory of paradise, but also opened access to heaven, i. e., to the State of the highest happiness. The human person should advance spiritually during the earthly life to become apt to accept the gift of the eternal happiness.